Strategy For Resolving Financing Problems In The Alfa Mabruk Wonorejo Pasuruan Syariah Cooperative - Jannah, Miftakhul; Aslikhah, Aslikhah; Sukamto, Sukamto (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2024)
Sharia cooperatives are part of sharia financial institutions (LKS) which are based on sharia principles. The main objective is to promote community welfare through a profit- and falah-oriented approach. This research aims to determine and analyze strategies for resolving problematic financing at the Alfamabruk Wonorejo Pasuruan sharia cooperative. This is important because if it is not handled immediately it can damage the cooperative's performance and become an obstacle in business development due to financial difficulties. This research is qualitative research with a descriptive approach in which researchers carry out field studies to obtain accurate information by conducting interviews, then from these results data analysis and data credibility are carried out in order to obtain good results. The results of the research concluded that the factors that cause financing problems are business failure, poor character of customers, misuse of capital, increasing unemployment due to the difficult economic situation, due to the Covid-19 disaster. The strategy used by the Alfamabruk Wonorejo sharia cooperative is through rescheduling, reconditioning, restructuring and using a personal approach.